Paleomagnetic record for the past 80 ka from the Mahanadi basin, Bay of Bengal. (January 2018) - Usapkar, A.; Dewangan, P.; Mazumdar, A.; Krishna, K.S.; Ramprasad, T.; Badesab, F.K.; Patil, M.; Gaikwad, V.V.
Graphical abstract: Highlights: Laschamp, Norwegian-Greenland Sea (I & II) excursion events are observed in the Mahanadi basin. The observed inclination anomalies are not associated with the changes in magnetic minerals/depositional environment. The excursions are often associated with a drop in paleointensity. The VGP path traced by Laschamp excursion shows a clockwise loop. Abstract: High resolution paleomagnetic investigations were performed on a 50.08 m long sediment core (MD161/20) from Mahanadi basin, Bay of Bengal. Core yielded reliable paleomagnetic results for top 20 m below seafloor (mbsf) which spans about 80 ka. Based on the analysis of rock magnetic data, the core is subdivided into five distinct Zones: Zone 1 and Zone 2 cover top 20 mbsf and do not show any abrupt change in magnetic mineralogy, concentration and grain size. Zones 3 and 5 show significant reduction in χLF, χARM and SIRM due to dissolution of magnetic minerals. Zone 4 shows moderate values of χLF and SIRM. The low value of χARM suggests that magnetic signal is mostly carried by magnetic grains in PSD/MD state. The paleomagnetic data for the top 20 mbsf show four prominent geomagnetic excursions at ∼9 mbsf, ∼13.5 to 15 mbsf, ∼16.3 mbsf and ∼18 to 18.2 mbsf. The age-depth relationship is established using stratigraphic correlation between well-dated sedimentary core NGHP-01-19B and the core MD161/20. The ages of the observed excursions correspond to ∼18 to 20 ka, ∼42 to 49 ka, ∼54 to 57 ka and ∼69 to 70 ka. The excursions at ∼42 to 49 ka, ∼54 to 57 ka, and ∼67 to 70 ka is similar to the known excursions the Laschamp and the split Norwegian-Greenland Sea events (NGS-I and NGS-II). The excursion at 18–20 ka is not observed globally and may be related to lithological/sedimentological changes occurring during last glacial maxima (LGM). The virtual geomagnetic path (VGP) of Laschamp excursion traces clockwise loop. All excursions identified in present study fall in the periods of relatively low paleointensity.